A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil - Reia, Lais; Benine, Ricardo C. (Zootaxa, 2019)
A new species of Hemigrammus is described from the upper Rio Negro, Amazon basin, Brazil. The new species is distinguished from all congeners by its unique color pattern consisting of a single humeral blotch clearly spaced from a conspicuous midlateral dark stripe, which extends from fifth or sixth anteriormost vertical scale row to the basis of the middle caudal-fin rays. Comments on its putative relationships are provided.